Analysis Of Excellent Service Innovation At The Air Nipis Sub-District Office, South Bengkulu District - Marisa, Wica; Indarti, Sri (GAYAKU PUBLISHER, 2024)
There are many aspects of national social life which are basically related to public services. Responsibility for providing essential public services, such as health care, education, and information technology, lies with the government. Facebook applications, WhatsApp groups and 24-hour services are some of the innovative public information facilities and services offered by the Elnipis Regency Government in South Bengkulu Regency. The aim of this research is to find new ways for the public sector to use the 24 hour service feature on the Facebook WhatsApp group application. A combination of descriptive and qualitative research methodologies was used in this research. Interviews, observations, and recordings related to Facebook applications, WA groups, and 24-hour services were used as data collection techniques. According to Rogers' (2003) theoretical approach, which proposes that users of the Facebook Metrics application, WA grub, and 24-hour service compliance benefit greatly from relative profitability, this data can then be examined qualitatively by examining all the data collected, which is supported by the results of the interviews . Both previous and current innovations are very easy; App users faced a little problem and had the opportunity to test it. It has amazing results and will be noticed by people at all social levels. Based on research results, the WA Facebook group application and 24-hour service show a high level of public service innovation. The five indicators of innovation used in this research are relative advantage, implementation, complexity, possibility of being tried, and possibility of being observed. There are two indicators that are not optimal, namely complexity and the possibility of trying